A case of acute myeloid leukemia with e6a2 BCR-ABL fusion transcript acquired after progressing from chronic myelomonocytic leukemia. (2017) - Yao, Jinjuan; Douer, Dan; Wang, Lu; Arcila, Maria E.; Nafa, Khedoudja; Chiu, April
Abstract: Philadelphia (Ph) chromosome is a cytogenetic hallmark of chronic myeloid leukemia (CML). Most patients with CML harbor either the e13a2 or e14a2 BCR-ABL fusion product, while a small subset of the cases expresses e1a2 or e19a2 transcripts. We report a patient with chronic myelomonocytic leukemia (CMML), initially Ph chromosome negative at presentation, with rapid disease progression to acute myeloid leukemia (AML) and appearance of Ph chromosome and BCR-ABL e6a2, a very uncommon fusion transcript. The AML was refractory to treatment with subsequent emergence and dominance of a Ph negative leukemic clone. The patient expired shortly after disease progression.